Pelatihan Kewirusahaan Berbasis Internet : Tips dan Trik Sukses Berbisnis Online Bagi Remaja Milenial di Desa Kaduara Barat Pamekasan - Aflahah Aflahah; Mohammad Imam Sufiyanto (PERDIKAN (Journal of Community Engagement), 2019)
The way to maximize the potential of youth entrepreneurial spirit is through the internet-based entrepreneurship training program "Tips and Tricks for Online Business Success for Millennial Youth in the West Kaduara Village". This program is a community service activity carried out in the form of training, as well as creating sustainable and independent activities to increase entrepreneurial interest for millennial youth in the West Kaduara Village. This program will take place on Sunday, August 3, 2019, which consists of five activities, namely Study Online Shop, Achievement Motivation Training and Succsess Story, understanding of online shop platforms and social media knowledge. The first stage is the online shop study, this activity aims to provide knowledge and capture program targets, after the targets are obtained, the program continues with the provision of training and skills on online-based entrepreneurship which includes platform knowledge and success stories, understanding of the online shop, and knowledge of social media in business management. After the target has skills in developing the business, then the provision of understanding of social media is carried out as a step towards the realization of the target to practice the entrepreneurial spirit that they have learned. The program's success criteria result from the enthusiasm of millennial adolescents in managing the business that has been given to the target, namely increasing the level of target knowledge about the meaning of entrepreneurship, increasing target commitment in implementing entrepreneurship programs, and increasing entrepreneurial desire from the target. Keywords: The Soul of Entrepreneurship; Social Media; Online Shop.